2002
DOI: 10.1070/qe2002v032n08abeh002271
|View full text |Cite
|
Sign up to set email alerts
|

New diode lasers with leaking emission in an optical cavity

Abstract: We recast the study of a closed string gas in a toroidal container in the physical situation in which the single string density of states is independent of the volume because energy density is very high. This includes the gas for the well known Brandenberger-Vafa cosmological scenario. We describe the gas in the grand canonical and microcanonical ensembles. In the microcanonical description, we find a result that clearly confronts the Brandenberger-Vafa calculation to get the specific heat of the system. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Irregularities in the intensity distribution can be explained with a relatively low optical quality of the substrates. The beam divergence of this DFB laser was found to be as large as ~5 mrad which is comparable to that obtained for semiconductor leaky-mode lasers, see for example [37,38].…”
Section: Resultssupporting
confidence: 74%
“…Irregularities in the intensity distribution can be explained with a relatively low optical quality of the substrates. The beam divergence of this DFB laser was found to be as large as ~5 mrad which is comparable to that obtained for semiconductor leaky-mode lasers, see for example [37,38].…”
Section: Resultssupporting
confidence: 74%
“…be a system of fundamental functions of equation (7). Then, due to the periodicity of the differential equation…”
Section: A Model Study Of the Characteristics Of Two-dimensional Lase...mentioning
confidence: 99%
“…Thus, the ultrasmall thickness of the layers in combination with a large number of interfaces between the layers and the alternation of layers of different materials leads to the appearance of multilayer nanostructures with unique structural features that are not present in the materials that make up the nanostructures in massive samples [1]. The manifestation of such features is associated with the detection of such physical properties in multilayer nanostructures as extremely high hardness [2], low transverse thermal conductivity [3], the effect of giant magnetoresistance (GMR) [4], divergence of the radiative characteristics of heterolasers with increasing temperature [5][6][7][8], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that it is possible to create edge-emitting lasers where just only the waveguide is involved in the lasing. For instance, in so-called leaky wave diode lasers [3,4] lasing is developed within a thin waveguide with an embedded active region (as in usual edge-emitting diode lasers), while the output emission is the emission leaking to a semiconductor substrate.…”
Section: Introductionmentioning
confidence: 99%